1990
DOI: 10.1177/008124639002000306
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of World View of Black and White South African Adolescent Pupils: Implications for Cross-Cultural Counselling

Abstract: Research on cross-cultural counselling and psychotherapy began to receive emphasis in the 1970s in the United States. In South Africa the need to devise relevant help for the majority black population and to contextualize psychological services is being increasingly addressed in the literature. In the present study differences in world view between black and white South African adolescent pupils ( n = 200) were investigated. The use of a scale to assess world view across culture indicated significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, little research has been done to demonstrate the validity of the questionnaire for the different ethnic and cultural groups in South Africa. Several studies during the 1980s and early 1990s indicated that black and coloured South Africans generally achieved lower scores than their white counterparts on measuring instruments such as the Career Maturity Inventory and the Career Development Questionnaire (Alexander, 1990;Beekman, 1989;Hickson & White, 1989;Reid-van Niekerk & Van Niekerk, 1990;Watson & Van Aarde, 1986). A recent study by Baloyi (1996) indicates that these differences can be ascribed to socioeconomic factors.…”
mentioning
confidence: 99%
“…However, little research has been done to demonstrate the validity of the questionnaire for the different ethnic and cultural groups in South Africa. Several studies during the 1980s and early 1990s indicated that black and coloured South Africans generally achieved lower scores than their white counterparts on measuring instruments such as the Career Maturity Inventory and the Career Development Questionnaire (Alexander, 1990;Beekman, 1989;Hickson & White, 1989;Reid-van Niekerk & Van Niekerk, 1990;Watson & Van Aarde, 1986). A recent study by Baloyi (1996) indicates that these differences can be ascribed to socioeconomic factors.…”
mentioning
confidence: 99%
“…'African culture' is said to be 'collectivist' or 'communalist' in that it is kinshipbased, and the interests of the social group are more highly valued than those of the individual (e.g. Bodibe & Sodi, 1997;Hickson, Christie, & Shmukler, 1990). Constructions of ubuntu -a fundamental humanity and caring for the well being of others -are often cited as evidence of an African communalism that is holistic, natural and loyal to ancestral tradition.…”
Section: African Communalism: Culture-as-therapy and Pathogenesismentioning
confidence: 99%
“…Given the unique situation of apartheid, there is ample evidence to believe that the Black South African cultural perspective (especially with regard to racial identity) is unique in itself (e.g., Hickson, Christie, & Shmukler, 1991). With particular reference to Blacks in South Africa and their unique situation, Harari and Beaty (1990) found that traditional questionnaire and survey approaches generated superficial or inaccurate data, leading to misconceptions of Blacks.…”
Section: The Ethnographic Approachmentioning
confidence: 99%